Analysis of the Effect of 4P Marketing Mix on Word of mouth, Purchasing Decisions and Repurchase Intention - Putri Adisti, Kirana; Waluyo, Minto (Dinasti Publisher, 2025)
This research aims to analyze the influence of the 4P marketing mix—product, price, promotion, and place—on Word of Mouth (WOM), purchase decisions, and repurchase intention among consumers of Kopi Keliling Surabaya. The study employed a quantitative approach using Structural Equation Modeling (SEM) with Maximum Likelihood estimation, involving 140 respondents who had made at least one purchase of Kopi Keliling products. The findings indicate that price and promotion significantly affect WOM and purchase decisions. However, the product and place variables were excluded from the final model due to multicollinearity issues and failure to meet validity criteria. WOM was found to have a significant impact on purchase decisions, while purchase decisions significantly influenced repurchase intention. In contrast, price and promotion did not show a direct significant effect on repurchase intention. The simultaneous regression equations suggest that promotion plays the most dominant role in shaping WOM, purchase behavior, and future repurchase interest. These results offer strategic insights for Kopi Keliling Surabaya in improving its marketing effectiveness by focusing on strong promotional activities and value-based pricing strategies. This study contributes to the understanding of marketing mix application in mobile coffee businesses and helps guide managerial decision-making in a competitive, dynamic, and consumer-driven market environment.